Ultrasound-guided lumbar plexus block versus transversus abdominis plane block for analgesia in children with hip dislocation: A double-blind, randomized trial - Sun Ke; Jin Mei; Zhang Xiaoguang (Open Medicine, 2022)
Lumbar plexus block is often used as analgesia for adult hip surgery, but it is rarely used in pediatric patients. This study aimed to compare the efficacy and feasibility of ultrasound-guided lumbar plexus block versus transversus abdominis plane block for postoperative analgesia in children with hip dislocation. Eighty children undergoing unilateral hip dislocation surgeries at our hospital from October 2019 to February 2021 were randomized to the lumbar plexus block group (group L) and transversus abdominis plane block group (group T). Compared with group L, the regional block time in group T was lower (8.0 ± 2.5 vs 11.5 ± 2.3 min, P < 0.05), and the ultrasound image definition was better (P < 0.05). There were no significant differences in mean blood pressure and heart rate within 24 h (all P > 0.05). Children’s Hospital of Eastern Ontario Pain Scale scores were lower in group L than in group T at 18–24 h only (all P < 0.05). The satisfying analgesia rate in group L was higher than in group T (87.5 vs 65%, P < 0.05). No regional block-related complications were found in both groups. Ultrasound-guided lumbar plexus block showed a longer postoperative analgesic effect in children with hip dislocation compared with transversus abdominis plane block.